Cerita Rakyat Lampung Di Kampung Tua Negara Batin Kecamatan Negara Batin Kabupaten Way Kanan Provinsi Lampung - Agustina, Eka Sofia; Ariyani, Farida; Zamzanah, Sarjinah; Prasetya, Rian Andri (UPI, 2020)
Everything related to the origin of a region's life cannot be separated from the lives of its Ancestors told from